Online experimental research on the psychological capital development of new venture entrepreneur under the COVID-19 pneumonia epidemic - Zeng, Na; Zhang, Ming; Fu, Shanna; Xiao, Qin; Javed, Tahira (Frontiers in Psychology, 2023)
The global economy has been severely traumatized by the COVID-19 pandemic, and new ventures are under tremendous pressure to survive. This paper explores whether structured reading materials and mindfulness intervention can develop entrepreneurs’ psychological capital and whether there are different effects on different development methods. We recruited 112 new venture entrepreneurs and carried out an online experiment using the experimental group, the control group, and the pre-test and post-test design; at last, 83 of whom participated in the process can be assessed for psychological capital development effect. The research findings indicated that structured reading materials could effectively improve the overall psychological capital of the subjects（t=-5.574，p<0.01） and impact in every dimension, including self-efficacy (Z=-2.858, p<0.01), hope (t=-3.560, p<0.01), resilience (t=-4.368, p<0.01) and optimism (Z=-3.300, p<0.01). In comparison, mindfulness intervention can improve the subjects’ overall psychological capital (Z=-3.293, p<0.01) and improve levels of self-efficacy (Z=-2.285, p<0.01), hope (t=-4.244, p<0.01), resilience (t=-3.167, p<0.01), but limited effect on the optimism (t=-1.955, p>0.05); In addition, there is no significant difference between structured reading materials and mindfulness intervention according to the statistical analysis.